2012
DOI: 10.5694/mja11.10363
|View full text |Cite
|
Sign up to set email alerts
|

The shortage of medical oncologists: the Australian Medical Oncologist Workforce Study

Abstract: oncerns are increasing in Australia and internationally that the supply of medical oncologists (MOs) is insufficient to meet the rising demand. 1-5 The only study of the medical and haematological oncology workforce in Australia was published in 2001. 6 This study found that there were 180 MOs in active practice in Australia (0.9 per 100 000 population), and an estimated shortfall of at least 40 medical and haematological oncologists. The best estimate of the number of MOs in Australia in 2009 was 311, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 8 publications
2
43
0
Order By: Relevance
“…In their cohort, the median annual consult load was approximately 260 for office patients only, but rose to 350 per oncologist if hospital inpatients were included. In a 2009 Australian survey, Blinman et al 6 reported an annual new consult workload of 280 for 94 Australian mos. Finally, a 2009 survey of 32 mos by the New Zealand Working Group reported an annual consult load of 220 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their cohort, the median annual consult load was approximately 260 for office patients only, but rose to 350 per oncologist if hospital inpatients were included. In a 2009 Australian survey, Blinman et al 6 reported an annual new consult workload of 280 for 94 Australian mos. Finally, a 2009 survey of 32 mos by the New Zealand Working Group reported an annual consult load of 220 4 .…”
Section: Discussionmentioning
confidence: 99%
“…We are not otherwise aware of any systematic study of the medical oncology workload in Canada. Moreover, we are aware of only three studies from other high-income countries (hics) that have explored these issues [4][5][6] . In those studies (from New Zealand, the United States, and Australia), the mo caseload was 220-280 new patients per year.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative methods of service delivery through the involvement of a range of health care professionals beyond medical-led services warrant consideration to meet the needs of an expanding cancer population, particularly in view of the obvious need for psychological supports experienced by patients who had multiple UPAs [37]. A variety of non-medical service initiatives is described in the literature, all of which demonstrate success in reducing UPA [7,18,29,38] and include symptom-focused home care nursing [29], community integrated case management of advanced practice nurses in oncology [38] and telephone access to specialised oncology nurses [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicate that metropolises with more beds tend to attract more physicians (18), as approximately 39.6% of physicians and 20.6% of patient beds are concentrated in Bangkok metropolis (22). Likewise, since Tehran is the capital with bigger health facilities than other provinces (23) having about 21.3% share of total cancer facilities, it is probably the reason to attract more oncologists (10). Although, there is no consensus on the ideal geographic concentration of physicians, the distribution of oncologists should meet the population's needs and provide sufficient accessibility to health care services (18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using medical council data might result in over-estimation or under-estimation of active physicians supply, especially in specialty areas. In addition to existing data banks, some studies have conducted surveys to determine the current and projected supply, demand and shortfall of medical oncologists (10). Other studies have synchronized medical council masterfiles with telephone directories to estimate the number of active physicians (6,11).…”
Section: Introductionmentioning
confidence: 99%